OPTIMALISASI KETAHANAN PANGAN MELALUI PENGELOLAAN TALAS DAN IKAN LOKAL DI DESA AIK BUKAQ, BATUKLIANG UTARA, LOMBOK TENGAH - Fanreza, Dhanu; Jurnal Wicara; Isfiyana, Niza; Aspara, Natha; Rizki, Bintang; Jodi, Fitria; Saputra, M. Ilam; Fitriani, Cici Aulia; Suciana, Nunung; Hardiyaningrum, Ratria; Jamil, M. Habibillah (Jurnal Wicara, 2025)
This community service activity was conducted in Aik Bukaq Village. Aik Bukaq Village is a tourist village where the majority of the population works as farmers and fish farmers. Ecologically, the Aik Bukaq tourist attraction is an ecotourism destination with an ecosystem with pristine natural potential. The village is home to abundant taro plants and freshwater fish. However, unfortunately, the surrounding community has not been able to utilize these resources optimally. Therefore, to support the utilization of the abundant fish and taro in the Aik Bukaq Village area and to increase community income, the following activities were carried out: (1) Making Dried Fish, (2) Making Taro Ice Cream, and (3) Digital Marketing Counseling.